Barker Hypothesis and Hypertension - Jebasingh, Felix; Thomas, Nihal (Frontiers in Public Health, 2022)
Early onset hypertension is one of many major medical disorders that have evolved over the current millennium across both the developing as well as the developed world. Though various mechanisms have been postulated for the evolution of hypertension in these individuals, one of the most relevant ones is that of low birth weight and its association with hypertension. Barker from historical evidence has postulated the foetal onset adult disease (FOAD) or Thrifty phenotype on Low Birth Weight (LBW) associated hypertension. Later, Brenner highlighted the importance of low nephron mass and future implications. In this review we elaborate the mechanisms that were postulated for LBW-related hypertension as well the potential antihypertensive therapy that may be used in these individuals.